Promoting The Value Of Vietnamese People Folk Beliefs: Policies And Recommend Solutions - Van, Vu Hong (The journal of contemporary issues in business and government, 2021)
Vietnamese beliefs hold a special place and play an important part in creating the character of Vietnamese culture. However, it also has certain limitations that need to be studied and considered to help authorities make certain adjustments to orient religious activities, and at the same time exploit the inherent values, contributing to the building and preservation of an advanced Vietnamese culture imbued with national identity. On the basis of researching the reality of belief activities of Vietnamese people across the country, the study analyzes the value of beliefs that bring to people’s lives, thereby proposing solutions to promote the positive and limit negative aspects in religious activities. Due to many objective and subjective reasons, the study focuses on analyzing only 3 typical Vietnamese folk beliefs: the worship of ancestor belief, the worship of Mother Goddess beliefs, and the worship of Village’s Tutelary God belief (Thành Hoàng làng).